Determining the Diagnostic Value of DWIBS in the Diagnosis of Breast Lesions Compared to Dynamic Contrast-Enhanced MRI: A Retrospective Observational Study - Maryam Farghadani; Safura Mozafari; Maryam Riahinejad; Mashid Haghighi; Reza Eshraghi Samani; Amir Mohammad Taravati; Koushan Rostami; Seyedeh Ghazal Shahrokh; Arezoo Sadeghian (Advanced Biomedical Research)
Background: Diffusion-weighted imaging with background body signal suppression (DWIBS) is a new imaging tool for the diagnosis of breast lesions. This study aims to compare DWIBS with contrast-enhanced magnetic resonance imaging (CE-MRI) sequences. Materials and Methods: Eighty consecutive patients underwent both CE-MRI and DWIBS images. DWIBS was assessed qualitatively and quantitatively using the apparent diffusion coefficient mapping. A threshold of 1.44 × 10-3 mm2/s was considered as a cutoff value between malignant and benign lesions. CE-MRI images were evaluated based on a combination of kinetic and morphological information and reported using Breast Imaging Reporting and Data System lexicon. Statistical analysis was performed for both sequences based on pathologic findings as a gold standard. Results: Fifty-five out of 80 lesions (69%) were benign, and 25 malignant lesions (31%) have been reported. The sensitivity, specificity, positive predictive value, and negative predictive value for CE-MRI were 100, 38, 42, and 100%, respectively, and those for DWIBS were 77, 70, 53, and 87%, respectively. By comparing DWIBS and CE-MRI data, no statistically significant difference was reported. Conclusion: DWIBS can be used as an effective alternative for breast CE-MRI in cases of contradictions of IV contrast injection.